The Capacity of the Regional Disaster Management Agency of Muaro Jambi Regency in the Prevention and Control of Forest and Land Fires in 2024 - Desinta, Puspa; Beriansyah, Alva; Sazeta, Mirza; Hapsa, Hapsa (Journal of Social and Policy Issues, 2025)
This study aims to analyse the capabilities of the Muaro Jambi Regional Disaster Management Agency (BPBD) and the efforts made to combat forest and land fires. Forest and land fires caused by natural and human factors cause environmental damage and result in ecological, economic, and socio-cultural losses. To effectively prevent and control such incidents, the Muaro Jambi BPBD must have strong institutional capabilities. This study uses a qualitative descriptive approach, with data collected through in-depth interviews and document analysis. Using the Kusumasari Capacity Framework, this study evaluates key indicators such as institutional structure, human resources, policy implementation, financial capacity, technical aspects, and leadership. The findings show that the Muaro Jambi BPBD has demonstrated commendable performance in fire prevention and control. However, several challenges remain, including inadequate infrastructure, limited human resources, and budget constraints, which hamper the agency's ability to operate optimally. In addition, public awareness of fire prevention remains uneven, and land clearing by burning is a major cause of fires, along with weather factors. To improve its capabilities, the Muaro Jambi Regional Disaster Management Agency has focused on strengthening cross-sector collaboration, increasing human resource capacity, and utilising technology to support more effective fire prevention and control strategies.